A 4-Channel Demultiplexer Based on 2D Photonic Crystal Using Line Defect Resonant Cavity. Issue 6 (1st November 2016) - Talebzadeh, Reza; Soroosh, Mohammad; Daghooghi, Tina
ABSTRACT: In this paper, a 4-channel demultiplexer based on 2D photonic crystal using line defect resonant cavity was proposed. The structure consists of one straight input and four vertical output waveguides with L3 cavities. The average quality factor is 4107.37, the crosstalk mean value is −27.33 db and the average transmission efficiency is 93.45%. Minimum pass band is 0.4 nm and channel spacing is around 2 nm. Cross section of the proposed structure is 360 so that the proposed multiplexer shows significant characteristics used in optical integrated circuits.